Coupled evolution of marine chemocline and nitrogen cycling on continental margins during the Middle Ordovician cooling - Chaogang Fang; Bolin Zhang; Mu Liu; Min Zeng; Haibo Huang; Chengcheng Zhang; Long Teng; Xiangli Wang; Guang-Yi Wei (Global and Planetary Change, 2026)

Evolution of wildfires under a greenhouse climate: A case study from the early Middle Jurassic in the Ordos Basin, China - Jianbo Hu; Si Chen; Mian Zhang; Chunhui Mu; Weixing Long; Tianyou Wang; Yingchun He; Xiaoming Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A circular agriculture model based on vegetable tailing fermentation broth: a case study of cabbage production - Junjie Cui; Rongrong Zhang; Mingle Yang; Tingting Mu; Shilei Luo; Long Li; Guobin Zhang (Bioresource Technology Reports, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Striking a balance: Grain yield and functional substances of black rice (Oryza sativa L.) under shading stress in tropical regions - Shaokun Song; Song Li; Zongli Liu; Yixue Mu; Long Chen; Heng Zhang; Kaiwen Qiu; Lixiao Nie (European Journal of Agronomy, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Integrating network pharmacology, molecular dynamics, and in vitro assays to unveil the mechanism of costunolide against gastric cancer - Chaohong Zhu; Qiuxiong Chen; Ying Li; Hui Wu; Qijun Ming; Mengyue Ma; Junjie Mu; Xiaoqin Long; Xian Yang; Xue Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Enhanced chlorine photolysis and 1H-benzotriazole degradation in water under the Far-UVC (UV222) irradiation - Jia-Jing Lyu; Qing Bai; Qian-Yuan Wu; Yu-Jia Nong; Mu-Da Han; Min-Yong Lee; Zhong-Quan Ren; Jiang-Lei Xiong; Wen-Long Wang (Journal of Environmental Chemical Engineering, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Metagenomic insights into the dynamics and persistence of antibiotic resistance genes in wastewater treatment plants - Yinming Mu; Chaoxuan Liao; Yunchuan Long; Yu He; Xiaoxin Cao; Long He; Juan Zhou; Yaqi Chen; Wen Wang; Shaoqi Zhou (Journal of Water Process Engineering, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Dehydrocostus lactone induces apoptosis and mitophagy in gastric cancer cells through the ROS-mediated mitochondrial pathway - Qiuxiong Chen; Ying Li; Junjie Mu; Qian Ming; Chaohong Zhu; Ziyue He; Mengyue Ma; Xiaoqin Long; Hui Wu; Baoli Qiu; Lihe Zhang; Xian Yang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Highly efficient Xe/Kr separation within a metal-organic framework featuring continuous molecule traps - Yan-Long Zhao; Xiang-Yu Li; Xuefeng Bai; Mu-Zi Li; Xin Zhang (Chemical Engineering Journal, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Defective bimetallic oxide Ce0.6Zr0.4O2 for simultaneous electrochemical detection and adsorptive removal of heavy metal ions - Dahui An; Junhua Zheng; Qing Wang; Mubai Liao; Shuchen Mu; Long Chen (Journal of Environmental Chemical Engineering, 2025)

Grain yield and functional substance content in colored ratoon rice system under low solar radiation stress in southern China - Shaokun Song; Heng Zhang; Long Chen; Yixue Mu; Song Li; Ye Tao; Zaid Ulhassan; Haider Sultan; Lixiao Nie (Field Crops Research, 2025)

Integration LC-MS/MS and molecular modeling techniques to elucidate the molecular mechanisms of goat whey protein-IgG interactions - Hongbo Li; Quan Gao; Xianjun Gao; Geng Long; Meng Bian; Shuo Feng; Shanbo Mu; Hongjuan Li; Jinghua Yu (Food Chemistry, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Synergistic Enhancement of Plant Drought Tolerance by PYL and ABA—A Review - Rongrong Zhang; Shilei Luo; Long Li; Tingting Mu; Peng Wang; Guobin Zhang (Journal of Plant Growth Regulation, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

A robust CMCNa-PAM salt-inhibiting double-network hydrogel for efficient solar interfacial evaporation - Junzhe Huang; Jianhua Zhou; Yang Long; Xiaojiang Mu; Zhixiang Zhang; Yanqing Zhu; Gang Xu; Jing Liu; Jun-Liang Chen; Lei Miao (Journal of Environmental Chemical Engineering, 2025)

Silicon Promotes Na+ Compartmentalization and Mineral Uptake in Zucchini Seedlings to Maintain Physiological Homeostasis and Alleviate Salt Stress - Rongrong Zhang; Guoshuai Wang; Shilei Luo; Long Li; Tingting Mu; Peng Wang; Guobin Zhang (Journal of Plant Growth Regulation, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Solar-driven evaporation based on regulation salt crystallization behavior for high-efficiency freshwater production and salt collection - Hailan Zhao; Xiaojiang Mu; Lu Yin; Zhixiang Zhang; Yang Long; Yitong Wang; Xiaoyang Wang; Jianhua Zhou; Lei Miao (Desalination, 2025)

A review of the interaction mechanisms between jasmonic acid (JA) and various plant hormones, as well as the core regulatory role of MYC2 - Tingting Mu; Shilei Luo; Long Li; Rongrong Zhang; Peng Wang; Guobin Zhang (Plant Science, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

A recursive segmentation model for bok choy growth monitoring with Internet of Things (IoT) technology in controlled environment agriculture - Chenchen Kang; Xinyang Mu; Aline Novaski Seffrin; Francesco Di Gioia; Long He (Computers and Electronics in Agriculture, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Enhanced chemiluminescence by carbon dots for rapid detection of bisphenol A and nitrite - Yujie Xiao; Xiaoqin Long; Xue Zhang; Junjie Mu; Qiuxiong Chen; Yuxian Mai; Ying Li; Hao Xue; Pengyang Song; Xian Yang; Hong Zheng (Food Chemistry, 2025)

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Chemotaxis gene of a bacterium impacts larval settlement and metamorphosis in the marine mussel Mytilus coruscus via c-di-GMP controlling extracellular protein production - Yu Tao; Jiayi Mu; Lihua Peng; Jin-Long Yang; Xiao Liang (Biofouling, 2024)

Enhancing energy yield and reducing environmental impact through co-hydrothermal carbonization of undehydrated sewage sludge and fungus bran - Shuai Guo; Jiyou Mu; Long Gao; Liya Ge; Grzegorz Lisak (Journal of Environmental Chemical Engineering, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Experimental Study on Mechanical Behavior, Fracture Characteristics, and Acoustic Emission Damage Characteristics of Sandstone Under Triaxial Multistage Stress Disturbance - Sheng-Qi Yang; Jing Yang; Zong-Long Mu; Guang-Jian Liu; Man Huang; Ke-Sheng Li; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Response of soil organic carbon to land-use change after farmland abandonment in the karst desertification control - Yating Mu; Runcheng Ye; Kangning Xiong; Yue Li; Ziqi Liu; Yidong Long; Lulu Cai; Qingping Zhou (Plant and Soil, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

A continuous polymerase chain reaction 3D spiral microreactor capable of facile and on-demand fabrication - Qiushuang Yang; Wenchao Zhou; Huan Li; Jialing Huang; Zeyuan Song; Long Cheng; Yihui Wu; Deqiang Mu (Analytica Chimica Acta, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

The number and position of unsaturated bonds in aliphatic aldehydes affect the cysteine-glucose Maillard reaction: Formation mechanism and comparison of volatile compounds - Wenbin Du; Yutang Wang; Qinghong Yan; Shuang Bai; Yatao Huang; Long Li; Yuwen Mu; Ashbala Shakoor; Bei Fan; Fengzhong Wang (Food Research International, 2023)

Transcriptome Analysis of Energy Supply Process During Seed Germination in Phyllostachys edulis - Juan Li; Xiangyu Li; Yucong Bai; Yali Xie; Long Li; Shaohua Mu; Jian Gao (Plant Molecular Biology Reporter, 2023)

Impacts of site real-time adaptive control of water-sensitive urban designs on the stormwater trunk drainage system - Xuli Meng; Xuan Li; Allan Charteris; Zhenyao Wang; Mu. Naushad; Long D. Nghiem; Huan Liu; Qilin Wang (Journal of Water Process Engineering, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Life cycle assessment of stone buildings in the Taihang mountains of Hebei province: Evolution towards cleaner production and operation - Lingege Long; Qingxiang Li; Zhenkun Gan; Jun Mu; Mauro Overend; Dayu Zhang (Journal of Cleaner Production, 2023)

Distribution of Li, Ga, Nb, and REEs in coal as determined by LA-ICP-MS imaging: A case study from Jungar coalfield, Ordos Basin, China - Bo Jiu; Wenhui Huang; Baruch Spiro; Ruilin Hao; Nana Mu; Long Wen; Huidi Hao (International Journal of Coal Geology, 2023)

Xenobiotic-sensing nuclear receptors as targets for phthalates-induced lung injury and antagonism of lycopene - Yu-Sheng Shi; Yi Zhao; Xue-Nan Li; Mu-Zi Li; Jin-Long Li (Chemosphere, 2023)

Study on the deactivation mechanism of HZSM-5 in the process of catalytic cracking of n-hexane - Mu He; Muhammad-Faryad Ali; Yue-Qin Song; Xiao-Long Zhou; Jin An Wang; Xin-Yao Nie; Zheng Wang (Chemical Engineering Journal, 2023)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Identification and validation of an ECERIFERUM2- LIKE gene controlling cuticular wax biosynthesis in cabbage (Brassica oleracea L. var. capitata L.) - Jialei Ji; Wenxue Cao; Long Tong; Zhiyuan Fang; Yangyong Zhang; Mu Zhuang; Yong Wang; Limei Yang; Honghao Lv (Theoretical and Applied Genetics, 2021)

Human growth hormone proteoform pattern changes in pituitary adenomas: Potential biomarkers for 3P medical approaches - Biao Li; Xiaowei Wang; Chenguang Yang; Siqi Wen; Jiajia Li; Na Li; Ying Long; Yun Mu; Jianping Liu; Qin Liu; Xuejun Li; Dominic M. Desiderio; et al. (EPMA Journal, 2021)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Using β-ocimene to increase the artemisinin content in juvenile plants of Artemisia annua L. - Mu Xiao; Rong Liu; Chenfeng Long; Ying Ruan; Chunlin Liu (Biotechnology Letters, 2020)

A GNSS/INS-integrated system for an arbitrarily mounted land vehicle navigation device - Mengxue Mu; Long Zhao (GPS Solutions, 2019)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Exploration and Sources of Bauxite Deposit in the Boloven Plateau, Southern Laos - Yongzhen Long; Xiaoyong Yang; Mu Yang; Dexian Zhang (Journal of Earth Science, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Contamination levels and human health risk assessment of toxic heavy metals in street dust in an industrial city in Northwest China - Yufeng Jiang; Leiping Shi; A-long Guang; Zhongfeng Mu; Huiying Zhan; Yingqin Wu (Environmental Geochemistry and Health, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Geotechnical characteristics of weathered granitic gneiss with geo-hazards investigation of pit excavation in Guangzhou, China - Mu Chen; Shui-Long Shen; Huai-Na Wu; Zhi-Feng Wang; Suksun Horpibulsuk (Bulletin of Engineering Geology and the Environment, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Genome-wide analysis of shoot growth-associated alternative splicing in moso bamboo - Long Li; Tao Hu; Xueping Li; Shaohua Mu; Zhanchao Cheng; Wei Ge; Jian Gao (Molecular Genetics and Genomics, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Degradation characteristics of permafrost under the effect of climate warming and engineering disturbance along the Qinghai–Tibet Highway - Hui Peng; Wei Ma; Yan-hu Mu; Long Jin; Kun Yuan (Natural Hazards, 2015)

Solid Lipid Particles for Oral Delivery of Peptide and Protein Drugs II – The Digestion of Trilaurin Protects Desmopressin from Proteolytic Degradation - Philip Carsten Christophersen; Long Zhang; Anette Müllertz; Hanne Mørck Nielsen; Mingshi Yang; Huiling Mu (Pharmaceutical Research, 2014)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Antigenic variation between Newcastle disease viruses of goose and chicken origin - Zhi-jie Li; Yang Li; Shuang Chang; Zhuang Ding; Lian-zhi Mu; Yan-long Cong (Archives of Virology, 2010)

Microbial production of 1,3-propanediol from glycerol by Klebsiella pneumoniae under micro-aerobic conditions up to a pilot scale - Hai-Jun Liu; Dai-Jia Zhang; You-Hai Xu; Ying Mu; Ya-Qin Sun; Zhi-Long Xiu (Biotechnology Letters, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Microbial production of 1,3-propanediol by Klebsiella pneumoniae using crude glycerol from biodiesel preparations - Ying Mu; Hu Teng; Dai-Jia Zhang; Wei Wang; Zhi-Long Xiu (Biotechnology Letters, 2006)

Fine mapping of Ath6, a quantitative trait locus for atherosclerosis in mice - Maureen K. Purcell; Jian-Long Mu; David C. Higgins; Ramu Elango; Harry Whitmore; Stephen Harris; Beverly Paigen (Mammalian Genome, 2001)